If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6r + -17 = -25 + 4r Reorder the terms: -17 + 6r = -25 + 4r Solving -17 + 6r = -25 + 4r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4r' to each side of the equation. -17 + 6r + -4r = -25 + 4r + -4r Combine like terms: 6r + -4r = 2r -17 + 2r = -25 + 4r + -4r Combine like terms: 4r + -4r = 0 -17 + 2r = -25 + 0 -17 + 2r = -25 Add '17' to each side of the equation. -17 + 17 + 2r = -25 + 17 Combine like terms: -17 + 17 = 0 0 + 2r = -25 + 17 2r = -25 + 17 Combine like terms: -25 + 17 = -8 2r = -8 Divide each side by '2'. r = -4 Simplifying r = -4
| 0=-5q-2q | | 5(8x+2y-6)= | | 7z-11=-3+9z | | -8x-8x=64 | | -3q+r+2-q-6r= | | 8.2=2.8(3x-2) | | a^2+9ab-10b^2=0 | | 4x-18=-7(8-6x) | | [x+5]=42 | | 0=x^2+11x-34 | | x^2+0.8x-4.16=0 | | -x=(-2/9) | | n-10=5/6-7-1/3n | | 45+2x=180 | | 5q+2y-1+3q-5y= | | 3d+2(5d+4)=47 | | -2(8+3a)=24-a | | y^8-32y^4+256=0 | | u^2+3uv=0 | | -3x^2+525x-19602=0 | | log(8)(-3s+12)=log(8)(-7s+4) | | 6(4+4a)=24-4a | | m^2-11mn+10n^2=0 | | p^2+4p-43=0 | | 3n^3+21n^2-5n-35=0 | | 16-5x=x-26 | | a^2+10ab+9b^2=0 | | x(x+2)-8=2x+17 | | 30u^4v^3/5u^5v^3 | | 450x=380+3500 | | -96=-3(-5x+7) | | X^2-4=22 |